In vitro evaluation of phytochemical, antioxidant, anti-inflammatory and anticancer properties of Suaeda maritima - R. Pavithra; Mohammad Rashid Khan; Mohd Shahanbaj Khan (Discover Applied Sciences)
Abstract Halophytes adapted to saline environments are rich sources of bioactive compounds with notable pharmacological potential. Suaeda maritima (L.) Dumort. a well-known halophyte, has been traditionally employed for its medicinal benefits. This study investigates the phytochemical composition and bioactive potential of S. maritima extracts obtained through sequential extraction using hexane, chloroform, methanol, and water. The primary objective is to assess the phytochemical constituents and evaluate the antioxidant, anti-inflammatory, and anticancer activities of these extracts. Among the different solvent extracts, the methanol extract exhibited the highest concentration of bioactive compounds. Quantitative analysis revealed that the methanol extract contained significant amounts of phenols (185.92 mg GAE g⁻1), flavonoids (453.84 mg QCE g⁻1), terpenoids (246.36 mg linalool Eq g⁻1), saponins (50.75 mg diosgenin Eq g⁻1), and steroids (96.74 mg stigmasterol Eq g⁻1). Antioxidant activity assessed via DPPH assay showed an IC50 of 165.72 µg mL⁻1 for methanol extract compared to ascorbic acid (115.06 µg mL⁻1). Anti-inflammatory activity measured through protein denaturation inhibition revealed an IC50 of 203.55 µg mL⁻1 for methanol extract compared to diclofenac sodium (169.33 µg mL⁻1). The in vitro cytotoxicity assay against A549 lung cancer cells demonstrated that the methanol extract exhibited significant activity, with an IC50 of 52.55 µg mL⁻1, compared to doxorubicin (38.84 µg mL⁻1). LC–MS/MS analysis identified twelve bioactive compounds in the methanol extract, including phenols, steroid derivatives, terpenoid derivatives, anthraquinones, glycoside esters, and flavonoids. In conclusion, the methanol extract of S. maritima exhibited notable antioxidant, anti-inflammatory, and anticancer properties, underscoring its promise as a rich source of novel bioactive compounds. Further studies should aim at isolating and identifying these active constituents and elucidating their mechanisms through detailed in vivo investigations to support the development of effective, natural therapeutic agents.